Política social para idosos no Brasil: o benefício de prestação continuada e a seguridade social - Sochaczewski, Jacques (2014)
This Thesis aims to analyze the Continuous Cash Benefit (BPC - Benefício de Prestação Continuada), a non-contributory Brazilian public policy of income transfer to the poor disabled and elderly, as well their interactions with the policy of social assistance and social security. The starting point was the general understanding of historical and conceptual issues about the development of social protection to the shaping of social policy and their studies, followed by an analysis of the Brazilian situation; then, through research, we sought to evaluate the incorporation of BPC by the Sistema Único de Assistência Social (SUAS - Single System of Social Assistance) in a sample of 21 municipalities in Rio de Janeiro state, Brazil. The study revealed advances in social assistance policy as a whole, and also in the BPC configuration towards expanding access, especially after the conformation of the National Social Assistance Policy (Política Nacional de Assistência Social) and the Single System of Social Assistance. However, the lack of social security, as planned in the 1988 Constitution, reduces the effectiveness of their social protection, which depends on developing more specific policies and especially on to guarantee rights and services that go beyond social assistance